Influence of self-curing method on the performance of aeolian sand semi-rigid base using SAP and evaporation retardant - Yicheng Zhu; Wei Li; Rong Li; Can Guo; Ke Wang; Jiamiao Guo; Rui He; Jiangjiang She (Case Studies in Construction Materials)
Road construction in desert not only confronts the scarcity of high-quality road materials and water resources but also faces the impact of complex climatic conditions. To address these challenges, this paper used aeolian sand as road base layer material, and developed a self-curing method for aeolian sand semi-rigid base layer by incorporating superabsorbent polymer (SAP) and evaporation retardant (ER). During material preparation, three curing conditions were established: low-temperature curing, medium-temperature curing, and standard curing. The impact of the SAP-ER self-curing method on the semi-rigid base layer made of aeolian sand was evaluated in terms of moisture interaction and strength development. The mechanism was explored using SEM and XRD tests. The results indicate that under the same curing conditions, all three curing measures reduce the water absorption rate of the samples. Moreover, all three curing measures enhance the mechanical properties of the aeolian sand semi-rigid base layers at both 7 days and 28 days, and the SAP-ER self-curing method improves the mechanical properties of the aeolian sand semi-rigid base layer most significantly. The water release from SAP can compensate for internal moisture loss, while ER can minimize the evaporation of moisture on the surface of the concrete by isolating it from dry environment. The SAP-ER self-curing method effectively reduces the impact of environmental factors on the aeolian sand semi-rigid base layer, particularly in low-temperature, drought, and large temperature difference environments. This research provides theoretical support for the promotion and application of aeolian sand in road base construction.